A Potential Antifungal Effect of Chitosan Against Candida albicans Is Mediated via the Inhibition of SAGA Complex Component Expression and the Subsequent Alteration of Cell Surface Integrity - Shih, Pei-Yu; Liao, Yu-Ting; Tseng, Yi-Kai; Deng, Fu-Sheng; Lin, Ching-Hsuan (Frontiers in Microbiology, 2019)
Due to the high incidence of nosocomial Candida albicans infection, the first-line drugs for C. albicans infection have been heavily used, and the emergence of drug-resistant strains has gradually increased. Thus, a new antifungal drug or therapeutic method is needed. Chitosan, a product of chitin deacetylation, is considered to be potentially therapeutic for fungal infections because of its excellent biocompatibility, biodegradability and low toxicity. The biocidal action of chitosan against C. albicans shows great commercial potential, but the exact mechanisms underlying its antimicrobial activity are unclear. To reveal these mechanisms, mutant library screening was performed. ADA2 gene, which encodes a histone acetylation coactivator in the SAGA complex, was identified. Transmission electronic microscopy images showed that the surface of chitosan-treated ada2Δ cells was substantially disrupted and displayed an irregular morphology. Interestingly, the cell wall of ada2Δ cells was significantly thinner than that of wild-type cells, with a thickness similar to that seen in the chitosan-treated wild-type strain. Although ADA2 is required for chitosan tolerance, expression of ADA2 and several Ada2-mediated cell wall-related genes (ALS2, PGA45 and ACE2) and efflux transporter genes (MDR1 and CDR1) were significantly inhibited by chitosan. Furthermore, GCN5 encoding a SAGA complex catalytic subunit was inhibited by chitosan, and gcn5Δ cells exhibited phenotypes comparable to those of ada2Δ cells in response to chitosan and other cell surface-disrupting agents. This study demonstrated that a potential antifungal mechanism of chitosan against C. albicans operates by inhibiting SAGA complex gene expression, which decreases the protection of the cell surface against chitosan.